How to conduct an effective peer review - Barczak, Gloria (How to guides, 2021)
"This crucial book guides academics and researchers through the process of peer reviewing manuscript articles, outlining the methods and proficiencies required to write a high-quality review. Gloria Barczak and Abbie Griffin specifically highlight the importance of becoming a first-rate reviewer to early career scholars. Beginning with a working definition of a high-quality review, subsequent chapters detail the financial, career and personal benefits of peer reviewing for researchers, outline editors' and authors' expectations of reviewers, and offer a template for reviewing manuscripts effectively. Next, the book explicates sets of questions to consider in reviewing each section of a manuscript and features examples of reviews for actual journal submissions by the authors. Comprehensive in its approach, this book will be crucial for any early career social scientist hoping to effectively join the peer review process and write high-quality, meaningful reviews, as well as seasoned academics wishing to refine their skills"--